2017
DOI: 10.1002/2016wr020024
|View full text |Cite
|
Sign up to set email alerts
|

Validating a universal model of particle transport lengths with laboratory measurements of suspended grain motions

Abstract: The mechanics of sediment transport are of fundamental importance for fluvio‐deltaic morphodynamics. The present study focuses on quantifying particle motions and trajectories across a wide range of flow conditions. In particular, a continuous model is presented that predicts particle travel distances for saltation and suspension based on Rouse number and relative grain roughness. By utilizing a series of eight video cameras in a plexiglass flume direct measurements of the distributions of particle travel dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 69 publications
0
22
1
Order By: Relevance
“…With transport of bed material in full suspension at the final stage of dune transition (EXP9), dune morphology becomes unstable and dune height diminishes due to flattening‐out of dune crests, associated with increasing flow velocity and decreasing flow depth (Naqshband et al, 2014; Reesink et al, 2018). Superimposed dunes vanish throughout the entire flume experiment, implying that they may not play an important role in washing out of host dunes through amalgamation processes, contrary to what is suggested in literature (e.g., Best, 2005; Naqshband et al, 2017).…”
Section: Resultscontrasting
confidence: 76%
See 1 more Smart Citation
“…With transport of bed material in full suspension at the final stage of dune transition (EXP9), dune morphology becomes unstable and dune height diminishes due to flattening‐out of dune crests, associated with increasing flow velocity and decreasing flow depth (Naqshband et al, 2014; Reesink et al, 2018). Superimposed dunes vanish throughout the entire flume experiment, implying that they may not play an important role in washing out of host dunes through amalgamation processes, contrary to what is suggested in literature (e.g., Best, 2005; Naqshband et al, 2017).…”
Section: Resultscontrasting
confidence: 76%
“…Recent advances further highlight the potential of maintaining high‐angle slipfaces on HADs by granular avalanches, whereas lower slipface angles of LADs have been interpreted as the product of loosely packed liquefied avalanches amplified by downslope currents (Kostaschuk & Venditti, 2019). Whereas sediment transport parameters (e.g., the Shields number and mobility parameter) in deep rivers are usually properly scaled in shallow flume experiments, the Froude number ( Fr )—undoubtedly the second most important bulk flow parameter next to the Reynolds number—is much larger in flumes ( Fr > 0.32) compared to deep rivers ( Fr < 0.32; Bradley & Venditti, 2017, 2019a; Fourrière et al, 2010; Holmes & Garcia, 2008; Julien, 1992; Naqshband et al,, 2014, 2016 2017). Although the Froude number is widely accepted to control dune stability and transition to USPB through both linear stability analysis (e.g., Colombini & Stocchino, 2008; Engelund, 1970; Kennedy, 1963; McLean, 1990; Shimizu et al, 2009) and empirical observations (e.g., Naqshband et al, 2017; Nelson et al, 2011; Simons & Richardson, 1966; Southard & Boguchwal, 1990), the physical controlling mechanism that links dune morphology to Fr remains unexplored to date.…”
Section: Introductionmentioning
confidence: 99%
“…The difference with saltating bed load particles is the size of jump lengths and the frequency of reentrainment. More recently, by tracking individual motion of grains over relatively large distances using a series of 8 video cameras, Naqshband et al () showed that the distribution of particle travel distances over plane bed lies along a continuum moving from bed load to suspended load dominant flow conditions. To better understand the mechanics of sediment transport over bed forms and to develop a widely applicable sediment transport model, future research may consider the nonuniform structure of dune wakes to better address the distribution of particle travel lengths over bed forms.…”
Section: Resultsmentioning
confidence: 99%
“…Dune length may then scale with particle excursion length when excursion length exceeds dune length. Some recent progress has been made in defining particle excursion lengths (Naqshband, McElroy & Mahon, 2017), but these are poorly defined over bedforms and it is unknown how these could affect dune dimensions.…”
Section: The Role Of Transport Stage On Bedform Dimensionsmentioning
confidence: 99%